THE APPLICATION OF ASSIGNMENT LEARNING GROUP METHODS THROUGH MICRO SCALE PRACTICUM TO IMPROVE ELEMENTARY SCHOOL TEACHER STUDY PROGRAM COLLEGE STUDENTS SKILLS AND INTERESTS IN FOLLOWING SCIENCE STUDY COURSES - Yudhie Suchyadi; Nita Karmila (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
The aim of the study is to increase students' interest and skills using the Group Assignment learning method through micro-scale practicums in Science courses. The study was conducted on Chemistry study subjects. The research subjects were 209 students of Elementary Teacher Education, Pakuan University . During the learning process, observations about student cooperation during the practicum were carried out. The results of observations of each cycle are evaluated as reflection material in the next cycle to improve students' skills and interests in accordance with the set targets. Data analysis was performed descriptively quantitative. Science practicum material is material in the Chemistry Study course on a micro scale. From the results of the T-test, there are significant differences. This means that the understanding of concepts and Science Process Skills increases after prospective teacher students experience the learning process of group assignments on Chemistry Study material on a micro scale. The results of understanding concepts, the average value increased from 62.42 to 86.68 and the science process skills increased the average value from 56.19 to 87.86. 94% students responded positively, namely agreed and strongly agreed that the process of science lectures with group assignments and micro-scale practicum. This can improve science process skills and understanding of materials in science courses at PGSD students.